Autonomous maintenance decision model for lathe machine using fuzzy analytical hierarchy process (AHP) method - Ahmadi Hamdan Musman (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2015)
Deterioration on production machine may lead to high production costs. One of the preventive maintenance strategies to reduce deterioration of machine is Autonomous Maintenance (AM). The aim of autonomous maintenance is to achieve a high degree of cleanliness, excellent lubrication and proper fastening on the machine. However, the conventional AM practice, the process of initial cleaning might increase the maintenance cost and the time required. Therefore, to make this process more effective and efficient, this study proposes an AM decision model using fuzzy Analytical Hierarchy Process (AHP) method to identify the critical components and to determine the right AM activities. A case study of a lathe machine is used to validate the model.